Latin American immigration and refugee policies: a critical literature review - Nieves Fernández‑Rodríguez; Luisa Feline Freier (Comparative Migration Studies, 2024)
Against the background of remarkable policy liberalization and the subsequent steep increase of forced displacement in Latin America, the literature on immigration and refugee policy in the region has gained momentum. Although largely overlooked, this literature has the potential to provide a corrective to political migration theory from the Global South. In this article we carry out a systematic, critical review of the regional literature along three thematic axes: legal analyses, normative and explanatory studies. Based on the review of 108 journal articles, we describe the characteristics, main contributions and research gaps of each thematic area. By analyzing legal norms and policy implementation gaps, existing studies on Latin America provide an understanding of migration policy over time and offer important empirical evidence for the advancement of political migration theory, challenging some of the main assumptions attributed to policies in the Global South. However, the lack of engagement with the broader literature and the absence of systematic analyses of its determinants and effects significantly limit the potential of this body of work. We close by making concrete suggestions of how future studies could fill existing gaps both in theoretical and empirical terms, and which methodological approach should be employed.
Keywords: 320; Immigration policy; Refugee policy; Latin America; Literature review; Global South